Bottled and packaged water. - Grumezescu, Alexandru Mihai; Holban, Alina Maria (Woodhead Publishing, 2019)
Bottled and Packaged Water, Volume Four in The Science of Beverages series, offers great perspectives on current trends in drinking water research, quality control techniques, packaging strategies, and current concerns in the field, thus revealing the most novel standards in the industry. As consumer demand for bottled and packaged water has increased, the need for scientists and researchers to understand how to analyze water quality, safety, and control are essential. This all-encompassing resource for research and development in this flourishing field covers everything from sensory and chemical composition, to materials and manufacturing.